Cross‐sectional and temporal relationships between bird occupancy and vegetation cover at multiple spatial scales. Issue 6 (1st September 2014) - Cunningham, Ross; Lindenmayer, David; Barton, Philip; Ikin, Karen; Crane, Mason; Michael, Damian; Okada, Sachiko; Gibbons, Philip; Stein, John
Abstract : Scale is a key concept in ecology, but the statistically based quantification of scale effects has often proved difficult. This is exemplified by the challenges of quantifying relationships between biodiversity and vegetation cover at different spatial scales to guide restoration and conservation efforts in agricultural environments. We used data from 2002 to 2010 on 184 sites (viz., site scale) nested within 46 farms (the farm scale), nested within 23 landscapes (the landscape scale). We found cross‐sectional relationships with the amount of vegetation cover that were typically positive for woodland birds and negative for open‐country birds. However, for some species, relationships differed between spatial scales, suggesting differences in nesting and foraging requirements. There was a 3.5% increase in the amount of native vegetation cover in our study region between 2002 and 2010, and our analyses revealed that some open country species responded negatively to these temporal changes, typically at the farm and/or site scale, but not the landscape scale. Species generally exhibited stronger cross‐sectional relationships with the amount of vegetation cover than relationships between changes in occupancy and temporal changes in vegetation cover. This unexpected result can be attributed to differences in habitat use by birds of existing vegetation cover (typically old‐growth woodland) vs. plantings and natural regeneration, which are the main contributors to temporal increases in vegetation cover. By taking a multi‐scaled empirical approach, we have identified species‐specific, scale‐dependent responses to vegetation cover. These findings are of considerable practical importance for understanding which species will respond to different scales of protection of existing areas of native vegetation, efforts to increase the amount of native vegetation over time, and both approaches together.